Analysis of similarities and differences of accessions belonging to Prunus domestica L. and P. insititia L. using endocarp dimensions - T. Milošević; N. Milošević (Вавиловский журнал генетики и селекции, 2025)
The endocarp or stone is the most stable morphological feature of the genus Prunus. However, the identification of plum types, groups and/or genotypes based on endocarp is complicated because of a wide range of variation and morphological transitional states. From this point of view, knowledge on the degree of variability within and between plum species or cultivars is a sine qua non for taxonomists and also for pomologists. In this study, different endocarp morphological traits, such as SW, linear dimensions (L, W and T), Da, Dg, S, V and shape indexes (φ, SI, E, RS, RO, DE and PI) were determined using analysis of variance and multivariate analysis (correlations and PCA). Results showed significant differences among accessions for all properties evaluated but with high overlaps in values. In most cases, the examined parameters were positively or negatively correlated with each other, indicating developmental relationships between them. Indeed, positive correlations were recorded for most variables, especially related to SW and endocarp linear dimensions. These results showed that the above properties could be a powerful indicator for selecting adequate endocarp size and shape in accessions, which may be used in taxonomic analysis. With an account of these correlations, PCA was employed to correctly estimate the endocarp size and shape and distribution, segregation and dispersion of accessions. All linear measurements and index values showed a normal or low variability at the individual level in most cases, with the exception of SW, V and PI in both European and Damson plums and S in Damson plums. Of the 15 examined parameters, European plum had significantly higher SW, L, T, Da, Dg, S, E, RO and PI values than Damson plum. In contrast, Damson plum had higher SI, RS and DE values, while W, V and φ were similar.